Capacity and Intensity Indicators to evaluate the effect of different crop sequences and cover crops on soil physical quality of two different textured soils from Pampas Region - Salazar Landea, María Paz (2022)
Soil physical degradation is a current problem in Molisols of the Pampas Region under no-tillage (NT), that has been related to over-simplified agricultural systems with scarce or no rotations and long winter bare fallows. Soil physical quality (SPQ) is a key factor of soil health and productivity, as it controls root development and air and water fluxes and storage in the soil, which in turn affect nutrient uptake and plant growth. Cover crops have been proposed as a companion agricultural practice to improve NT performance and SPQ. The aim of this study was to evaluate the effect of the inclusion of winter cover crops in different cropping sequences on capacity and intensity indicators of SPQ in two soils of different texture under NT and to compare it with different traditional crop sequences, including non-agricultural plots. SPQ was evaluated at two different sites, one with a silty loam Argiudoll and the other with a sandy loam Hapludoll. Treatments included plots with and without cover crops, with different summer crop sequences (continuous soybean and corn – soybean rotations). Also, a corn – wheat/soybean rotation with and without pastures was evaluated. All treatments had more than 15 years under the same management. We measured soil organic carbon (SOC), and capacity SPQ indicators (bulk density, total porosity, pore size distribution, air capacity, plant available water, relative field capacity and S index). We also measured dynamic SPQ indicators derived from field infiltration tests (saturated and near saturation hydraulic conductivity, effective macro and mesoporosity, and porosity connectivity indexes for different pore families). On the silty loam Argiudoll, cover crops increased SOC but failed to improve SPQ. This was related to soil physical degradation and the low ability of these soils for structure regeneration. On the sandy loam Hapludoll, cover crops had mixed effects on SOC and pore size distribution, but increased near saturation hydraulic conductivity, in the case of the corn – soybean rotation with cover crops, reaching values similar to those of a natural grassland.